Selected areas in cryptography : 14th international workshop, SAC 2007, Ottawa, Canada, August 16-17, 2007, revised selected papers - Adams, Carlisle 1961-; Miri, Ali; Wiener, Michael (New York : Springer, 2007)
PSZJBL